Analysis of the Effects of Influencer Marketing, Consumer Trust, and Content Quality on Purchase Decisions on TikTok Shop Indonesia (Jurnal Bisnis dan Manajemen West Science, 2026)
The rapid development of social commerce has transformed the way consumers discover, evaluate, and purchase products through digital platforms. This study analyzes the effects of influencer marketing, consumer trust, and content quality on purchase decisions on TikTok Shop Indonesia. A quantitative research design was employed using a survey method involving 175 respondents who had experience purchasing products through TikTok Shop. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using IBM SPSS Statistics version 25. The analysis included validity and reliability testing, classical assumption testing, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results show that influencer marketing has a positive and significant effect on purchase decisions, consumer trust has a positive and significant effect, and content quality also has a positive and significant effect. Simultaneously, the three independent variables significantly affect purchase decisions, with an R² value of 0.692. Consumer trust emerged as the strongest predictor. These findings indicate that successful social-commerce strategies on TikTok Shop should combine credible influencer communication, strong consumer trust, and high-quality product content to strengthen consumer purchase decisions.
Keywords: Influencer Marketing; Consumer Trust; Content Quality; Purchase Decision; TikTok Shop